A Classification Approach to the Growth of the Inter-Regional Agricultural Sector in East Nusa Tenggara Province - Yandri Erikson Edon; Wiendiyati Wiendiyati; Johanna Suek; Damianus Adar (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2021)
In terms of gross domestic product and labor absorption, the agriculture sector is the most important in East Nusa Tenggara (NTT) Province’s. The study's goal is to figure out how much the agricultural sector is growing and categorise it using Klasen Typology. The data utilized is a time series of agriculture industry growth from 2010 to 2019. The method of data analysis is employed. Klassen Klassifikasi Klassen with a matrix twice that cross-connects the expansion of the agriculture industry and its contribution to gross domestic product throughout East Nusa Tenggara areas. The comparison data is based on data on the development of sectors in Indonesian provinces that were chosen at random. The findings revealed that the agriculture sector in East Nusa Tenggara Province’s is reasonably stable, with minor expansion. According to the Klassen Classification, quadrant one consists of four regency’s: Ende regency, Kupang City, Lembata regency, and Sabu Raijua regency, all of which have advanced agricultural sectors. In the second quadrant, there are nine regency’s with advanced but depressed agricultural growth. There is one regency’s in the third quadrant classified as having a rapidly increasing agricultural sector. Six regency’s are classified in the fourth quadrant, with the agricultural sector lagging behind. Efforts to enhance the classified sector lag behind the higher agriculture sector, and the government is called upon to help. The function is played by improving the quality of human resources as well as the facilities and infrastructure that enable the agricultural sector's development.